EFEKTIVITAS METODE BLENDED LEARNING DALAM PENDIDIKAN KEPERAWATAN DI LABORATORIUM - Siti Fatimah; Samsiah; Putra Adi Syani (NURSE: Journal of Nursing and Health Science, 2025)
Background: This study aims to determine the effectiveness of the blended learning method in nursing education in the Nursing Laboratory during the Covid-19 pandemic. Method: This study used a quantitative approach by distributing research questionnaires to determine the level of effectiveness of the blended learning method in nursing education at UIN Jakarta. Results: results of this study indicate that overall the level of effectiveness of the blended learning method in nursing education at UIN Jakarta is good and effective. If you look at the indicators, they are already quite good, such as the indicators of interest or attention, relevance, and literacy towards ICT, the percentage of which has reached above 70%, even for indicators of literacy towards ICT itself, it can reach a percentage of more than 80%. However, it is very unfortunate when viewed from the confidence indicator, the value obtained is still below 70%, which is 68%.. Conclusion: The conclusion is overall the level of effectiveness of the blended learning method in nursing education at UIN Jakarta is good and effective. Keywords : blended learning; covid19; affectiveness; nursing; pandemic